Community-Based Recommendations to Improve Customer Turnout at a Non-Profit Grocery Store. (29th May 2020) - Daniel, Leena; Hinman, Sarah; Gunen, Bengucan; Harper, Kaitlyn; Poirier, Lisa; Gittelsohn, Joel
Abstract: Objectives: Aimed at improving healthy food access in a low-income neighborhood, the Salvation Army's first non-profit grocery store in Baltimore City has so far failed to attract a large customer base. The store averages just 140 customers daily and serves 500 unique families weekly, with an average transaction of $14. This study explored reasons for low usage from the perspective of community members and suggests solutions. Methods: Mixed-methods formative research was conducted at DMG Foods. In-depth interviews were conducted with store staff (n = 5), wholesalers (n = 3), local store non-users (n = 4), and store users (n = 9).Interviews focused on purchasing habits, observations, prices, marketing efforts, quality of food, location, and convenience. Direct observations of store operations (n = 8) and a short demographic survey of store users with loyalty cards (n = 119) and without loyalty cards (n = 33) was also completed. All in-depth interviews were coded and analyzed using ATLAS.ti v8.4.18. Results: The survey results indicated that the average amount spent at DMG Foods per loyalty customer within the last 30 days was $82. Only 11% survey respondents reported using DMG for all their grocery shopping. Reasons given for low store usage, included: (a) prices at DMG Foods are not low; (b) Non-users do not perceive DMG Foods as a food store; and (c) food quality concerns. In light of these responses, we made several recommendations, including: (a) make displays showing price differences between DMG Foods and other competitors; (b) place rebranded signs outside the store to indicate that DMG Foods is a grocery store; and (c) improve and maintain the quality of produce and meat in store. Additionally, store management should negotiate with wholesalers and distributors to obtain competitive wholesale prices. Conclusions: The results of this study will be used to inform DMG Foods and to help Salvation Army refine their non-profit grocery model as they expand it to other locations in Baltimore and across the United States. Funding Sources: Johns Hopkins University Bloomberg School of Public Health Department of International Health.